Analisis Pengaruh Modal Usaha, Lokasi, Lama Usaha, dan Tenaga Kerja Terhadap Pendapatan Pedagang Modern di Wilayah Gwalk Surabaya Tahun 2020 - sani, Amalia Tiara; Pratomo, Gigih (Economie: Jurnal Ilmu Ekonomi, 2025)
This research discusses the factors that influence the income of street vendors at Gwalk Surabaya with the aim of analyzing the effect of venture capital, location, length of business and labor, partially and simultaneously, have a significant effect on the income of street vendors at Gwalk Surabaya. The population in this study were all modern traders in the G-Walk Region of Surabaya in 2020, totaling 74 street vendors, using the Slovin formula, the number of samples taken in this study were 62 modern traders in the G-Walk Region of Surabaya in 2020. The method used is multiple linear regression analysis. Based on the results of the analysis and discussion, it can be concluded that, business capital has no effect on merchants 'income, location has no effect on merchants' income, length of business affects traders 'income, labor affects traders' income and variables. Business capital, location, length of business, labor together (simultaneously) have a effect on the dependent variable, namely merchant income modern traders in the G-Walk Region of Surabaya.